The Implications of Steady State Growth for Endogenous and Embodied Technological Change - John S.Lane (Queen's University, Department of Economics, 1970)
The concern with this paper is with necessary, rather than sufficient, conditions for the existence of steady state growth paths.
Keywords: 330